Optimization of cost effectiveness for slope stability - Afiq, Mohamad Nor (2010)
The development of infrastructure in Malaysia have been expand and more development within slope area were build widely that cause many slope failures. The dilemma that engineers nowadays face are to determine the suitability of the analysis methods and construction cost that is one of the main problems that cause lack of quality in construction of any infrastructure especially in slopes area. The knowledge of analysis and design of slope stability and the suitability of the slope protection used has been crucial to prevent any disaster happen. There were different methods used for slope stability analysis such as Ordinary, Bishop, Janbu,, Spencer, Sharma etc including various types of slope protection used in Malaysia occording to the suitability and costing. The objectives of this study are to compare the various methods of slope stability analysis used and hence determine the optimum cost for the selected slope protection. This study was made based on two selected slopes at Lot 4189, Bandar Tanjong Bungah, Jalan Selari Pantai Utara, Pulau Pinang using Ordinary, Bishop, Janbu dan Morgenstern-Price methods. The analysis were performed by using software GeoStudio 2007. The result of the analysis showed that Morgenstem-Price method was the realistic and reasonable method that can be used in analysing both of the selected slopes while Reinforced concrete retaining wall gives the optimum cost for both selected slopes.